Assessment of gamma radiation exposure of beach sands in highly touristic areas associated with plutonic rocks of the Atticocycladic zone (Greece). (October 2016) - Papadopoulos, A.; Koroneos, A.; Christofides, G.; Papadopoulou, L.; Tzifas, I.; Stoulos, S.
Abstract: This study aims to evaluate the activity concentrations of 238 U, 226 Ra, 232 Th, 228 Th and 40 K along beaches close to the plutonic rocks of the Atticocycladic zone that ranged from 15 to 628, 12-2292, 16-10, 143, 14-9953 and 191-1192 Bq/kg respectively. A sample from island of Mykonos contained the highest 232 Th content measured in sediments of Greece. The heavy magnetic fraction and the heavy non-magnetic fraction as well as the total heavy fraction, were correlated with the concentrations of the measured radionuclides in the bulk samples. The heavy fractions seem to control the activity concentrations of 238 U and 232 Th of all the samples, showing some local differences in the main 238 U and 232 Th mineral carrier. Similar correlations have been found between 238 U, 232 Th content and rare earth elements concentrations. The measured radionuclides in the beach sands were normalized to the respective values measured in the granitic rocks, which at least in most cases are their most probable parental rocks, so as to provide data upon their enrichment or depletion. Since the Greek beaches are among the most popular worldwide the annual effective dose equivalent received due to sand exposure has been estimated and found to vary between 0.002 and 0.379 mSv y −1 for tourists and from 0.018 to 3.164 mSv y −1 for local people working on the beach. The values corresponding to ordinary sand samples are orders of magnitude lower than the limit of 1 mSv y −1, only in the case of heavy minerals-rich sands the dose could reach or exceed the recommended maximum limit. Highlights: HREE's are correlated with 238 U and 232 Th → connection with minerals zircon or garnet The annual equivalent dose varies between 0.002 and 0.379 mSv y −1 for tourists. The annual equivalent dose varies between 0.018 and 3.164 mSv y −1 for local people. A sample from Mykonos bears the highest recorded Th content in sediments of Greece.